2010
DOI: 10.5483/bmbrep.2010.43.3.193
|View full text |Cite
|
Sign up to set email alerts
|

ZNF552, a novel human KRAB/C2H2 zinc finger protein, inhibits AP-1- and SRE-mediated transcriptional activity

Abstract: In this study, we report the identification and characterization of a novel C2H2 zinc finger protein, ZNF552, from a human embryonic heart cDNA library. ZNF552 is composed of three exons and two introns and maps to chromosome 19q13.43. The cDNA of ZNF552 is 2.3 kb, encoding 407 amino acids with an amino-terminal KRAB domain and seven carboxyl-terminal C2H2 zinc finger motifs in the nucleus and cytoplasm. Northern blotting analysis indicated that a 2.3 kb transcript specific for ZNF552 was expressed in liver, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Recent experimental studies have demonstrated that several KRAB-containing proteins such as zinc finger protein 552 (ZNF552) (407 amino acids at length with one KRAB domain at the amino terminal and seven C2H2 zinc finger motifs at the carboxyl terminal), ZNF328 (792 amino acids at length with a N-terminal KRAB domain and classic C-terminal C2H2 zinc finger motifs), and ZNF649 (505 amino acids of protein with N-terminal KRAB domain and C-terminal C2H2 zinc finger motifs) significantly inhibited serum response element (SRE) and AP-1 activities in COS-7 kidney fibroblast cells [124,125,126]. AP-1 is one key transcription factor for redox signaling pathway.…”
Section: Molecular Mechanisms Of Zinc As An Anti-oxidative Stress mentioning
confidence: 99%
“…Recent experimental studies have demonstrated that several KRAB-containing proteins such as zinc finger protein 552 (ZNF552) (407 amino acids at length with one KRAB domain at the amino terminal and seven C2H2 zinc finger motifs at the carboxyl terminal), ZNF328 (792 amino acids at length with a N-terminal KRAB domain and classic C-terminal C2H2 zinc finger motifs), and ZNF649 (505 amino acids of protein with N-terminal KRAB domain and C-terminal C2H2 zinc finger motifs) significantly inhibited serum response element (SRE) and AP-1 activities in COS-7 kidney fibroblast cells [124,125,126]. AP-1 is one key transcription factor for redox signaling pathway.…”
Section: Molecular Mechanisms Of Zinc As An Anti-oxidative Stress mentioning
confidence: 99%
“…19 Many zinc finger proteins have been demonstrated to be involved in transcription. 20 ZNF432 has been found to be associated with inflammatory bowel disease, at P= 8.3 × 10 −5 . 21 Thus, further study of these zinc finger proteins may provide insight on the mechanisms by which inhaled corticosteroids influence bronchodilator response.…”
Section: Discussionmentioning
confidence: 98%
“…The ZNF proteins have a large number of motifs that include Cys2-His2, GATA, RanBP, A20, LIM, MYND, RING, PHD, and TAZ. Of these, the most common motifs are the Cys 2 -His 2 domain-containing ZNF proteins [4,5]. On the other hand, another conserved domain present in one-third of all ZNF proteins [6] is Krüppel-associated box (KRAB) [7].…”
Section: Introductionmentioning
confidence: 99%